Pengaruh Fraud Hexagon Model Terhadap Kecurangan Laporan Keuangan - Oktavianus Andika Putra; Hexana Sri Lestanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to examine the effect of the fraud hexagon model on fraudulent financial statements. Financial statement fraud is measured by the Beneish M-score, while the fraud hexagon model is measured by pressure which is proxied by external pressure and financial stability, capability which is proxied by change in director, opportunity which is proxied by inefective monitoring, razionalitation which is proxied by change in auditor, arrogance which is proxied by the Frequent number of CEO's picture, collusion proxied by political connections. Quantitative methods are used in this study using secondary data sources. Researchers took data on companies from 2019 to 2021 and used the unit analysis of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The method of determining the sample in this study using purposive sampling. Data analysis used as hypothesis testing is multiple regression analysis. The results of this study indicate that pressure is proxied by financial stability and opportunity is proxied by inefective monitoring of audit committees and has a positive effect on fraudulent financial statements, while pressure is proxied as external pressure, capability is proxied as change in director, razionalitation is proxied as change in auditors, arrogance is proxied frequent number of CEO photo, collusion proxied by political connections, has no effect on fraudulent financial statements.